Natural and Synthetic Flavylium-Based Dyes: The Chemistry Behind the Color - Cruz, Luis; Basílio, Nuno; Mateus, Nuno; de Freitas, Victor; Pina, Fernando (Chemical reviews, 2022)
Flavylium compounds are a well-known family of pigments because they are prevalent in the plant kingdom, contributing to colors over a wide range from shades of yellow-red to blue in fruits, flowers, leaves, and other plant parts. Flavylium compounds include a large variety of natural compound classes, namely, anthocyanins, 3-deoxyanthocyanidins, auronidins, and their respective aglycones as well as anthocyanin-derived pigments (e.g., pyranoanthocyanins, anthocyanin-flavan-3-ol dimers). During the past few decades, there has been increasing interest among chemists in synthesizing different flavylium compounds that mimic natural structures but with different substitution patterns that present a variety of spectroscopic characteristics in view of their applications in different industrial fields. This Review provides an overview of the chemistry of flavylium-based compounds, in particular, the synthetic and enzymatic approaches and mechanisms reported in the literature for obtaining different classes of pigments, their physical-chemical properties in relation to their pH-dependent equilibria network, and their chemical and enzymatic degradation. The development of flavylium-based systems is also described throughout this Review for emergent applications to explore some of the physical-chemical properties of the multistate of species generated by these compounds.